Effect of organizational culture on organizational performance: The case of security sector - Rodrigues, A.; Pereira, L.; Costa, R.; Martins, L.; Gonçalves, R. (XI PostGraduate Conference in Management, Hospitality and Tourism - Book of abstracts, 2020)
Today’s business world is characterized by its constant rapidly changing environment, facing a very competitive economic context, making it crucial for the achievement of business success to understand, timely, what drives its results, namely its performance. Organizational performance may be affected by several number of variables and the understanding of these variables are decisive for business management. This research aims to address and measure organizational performance, understanding if and how much it is influenced by organizational culture, as well as if employee work engagement mediates the mentioned relationship.